La deforestación, una amenaza para los parques nacionales naturales de Colombia (2022)
Climate change is a cross-cutting issue that has reflected its impact not only in the environmental sector, health standards have set off alarms, water and air quality have been affected, not counting the extinction of species and the state of danger in which many times they are currently worldwide. In Colombia, as well as in many countries, one of the main generators of climate damage is deforestation, since the issuance of Law 99 of 1993 and before with the ratification of several international treaties, it has been proposed in theory, to conserve and strengthen Some areas that have been gradually declared as National Natural Parks of Colombia, these to date have functioned as the lungs of the Country, however, the figures show that every year deforestation increases alarmingly inside and outside these protected areas. Therefore, it is important to identify from the point of administrative law the institutional action, the review of the regulations, the importance that from the regulatory point of view has been generated to care for and expand areas based on environmental protection, prioritizing the identification protection mechanisms that can currently be implemented, the factors that generate deforestation, the role played by society and the responsibility that could be attributed to the state.Keywords (En cursiva). el resumen va acompañado de las palabras claves (5 como mínimo), que serán las que tengan más importancia en la investigación.